Beekeeping in Nepal: Assessing policy effectiveness and pathways for sustainable growth - Kafle, Nischal (Nepal Public Policy Review, 2025)
Beekeeping holds significant potential for enhancing rural livelihoods, increasing agricultural productivity, and conserving biodiversity in Nepal. Although honey production in the country has grown notably between 2012/13 and 2022/23, the sector continues to face persistent challenges in both production and marketing. Nepal still imports more honey than it exports, revealing a substantial gap between its potential and actual performance. This study critically examines key policies, including the Bee Promotion Policy 2017, National Agriculture Policy 2004, Agribusiness Promotion Policy 2007, and the Agriculture Development Strategy (2015-2035), using a descriptive-analytical approach to assess their effectiveness in supporting the beekeeping sector. Qualitative data were collected from 12 respondents representing government agencies, research institutions, and farming communities. The analysis focuses on eight key areas: institutional development, species conservation, infrastructure and financing, information dissemination, capacity building, product quality, market access, and research advancement. Findings indicate that while supportive policies exist, their implementation remains weak due to institutional overlap, poor coordination, inadequate funding, limited research emphasis, a shortage of technical publications, insufficient technical support, and low awareness and capacity among grassroots beekeepers. The study concludes that a more integrated, farmer-centric, and evidence-based policy approach is essential to fully realize the potential of beekeeping in Nepal. It recommends enhancing policy coherence, investing in innovative technologies, and improving market competitiveness to promote beekeeping as a sustainable and profitable enterprise.